Perancangan Desain Furniture Bertema Masyarakat Pesisir pada Bangunan Publik di Kenjeran Park - Gabriella Yolanda Kurnianto; Andereas Pandu Setiawan; Frenky Tanaya (Intra, 2018)
Kenjeran Park is one of the important historical landmark in East Java. However, the facilities has deterioriated over the years causing it to lose its appeal as a tourist destination, which is a shame as it is a place that carries a significant historical values. This design project is done with the aim of creating product ideas which will replace the existing facilities in Kenjeran Park. The main focus of the design will be comfort and durability in order to restore the people perception of the location and preserve its status as a cultural icon. The issue in Kenjeran Park mainly stems from the material used in the interior product design. Most of the products are made from plastic hence, it is unable to withstand the deterioriation caused by nature and also lack the aesthetic appeal as it is mainly geared towards mass production. Problems that exist in Kenjeran Park is because the existing interior products are plastic-based products where the products are made from plastic material can not stand the weather especially if placed in Kenjeran Park which is a beach area where the air is corrosive.Also, this design will also draw inspiration from the lifestyle of the people in that area creating a design which has variety and also aesthetically pleasing. Hence while innovating in terms of material that is being used to tackle the existing problem, it also helps showcase the cultural values of the area by drawing inspiration from them. Therefore, this design project can hopefully assist in government effort in redeveloping the area.